Field deployable sensors for health monitoring using colorimetric and chemiluminescence techniques - Singh, Priya (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Field deployable; sensors for health monitoring; using colorimetric; and chemiluminescence techniques